Przemiany i perspektywy potencjału egzogenicznego miasta-regionu - Miszczak, Katarzyna (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The main aim of this article is an attempt of presentation of development's prospects of city-region's exogamic potential. The functional structure of chosen settling unit was characterized through classification of individual functions, and next three sectors in urban economy were differed. On the basis of research conducted and deliberations the author states that the utilization of new external conditionalities, connected first of all with European integration’s process and globalization, and internal ones deterrnined by net structure forming currently in Poland, mean a huge chance facilitating conversions of given centre's exogamic potential. The author emphasizes the fact that dynamically progressing process of Polish space’s metropolization favours ventures which are undertaken in this range. Presented matters, opinions and conclusions were depicted in synthetic form by reason of the limited volume of the paper. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 248-258